Circular RNAs perspective: exploring the direction of immunotherapy for colorectal cancer - Cao, Yanlin; He, Yuxing; Liao, Lingshan; Xu, Lixin (Frontiers in Oncology, 2025)
Circular RNAs (circRNAs) are multifaceted molecules that play a pivotal role in regulating gene expression at both transcriptional and post-transcriptional levels. Their expression is highly tissue-specific and developmentally regulated, making them critical players in various physiological processes and diseases, particularly cancer. In colorectal cancer, circRNAs exhibit significantly dysregulated expression patterns and profoundly influence disease progression through diverse molecular mechanisms. Unraveling the complex roles of circRNAs in modulating colorectal cancer immunotherapy outcomes highlights their potential as both promising biomarkers and therapeutic targets. Moving forward, advancements in circRNA-based therapeutic strategies and delivery systems are poised to transform precision medicine, enabling early colorectal cancer diagnosis and improving patient prognosis.